Evaluating production process improvement strategies in a manufacturing SME: A case study - Ahmad Nazif, Noor Kamar; Cheng, Jack Kie; Syed Radzi, Rahamaddulla; Siti Zubaidah, Ismail (Learning Gate, 2024)
Growing competition and changing customer demands are driving manufacturers to rethink their production processes and adopt better improvement strategies. While larger manufacturers have successfully used advanced technologies to make their processes more efficient and customer focused, implementing these technologies requires significant investments in infrastructure, training, and system upgrades. This poses major challenges, especially for small and medium enterprises (SME). This study examines an SME specializing in the manufacturing of aluminum casting products. The company struggles to shorten the extended production time for its high-volume products to achieve the desired production planning targets. To address these challenges, the research utilizes discrete-event simulation (DES) modelling to predict how the production system behaves under several improvement strategies. The use of DES in this study has yielded promising results. The outcomes from proposed improvements demonstrate a remarkable 71% reduction in total production time required to produce monthly planned quantity, significantly enhancing existing production capacity. The simulation technique helps identify bottlenecks, address inefficiencies and evaluate different improvement scenarios in the production processes. It minimizes disruptions to operations, and supports the company decision-makers in selecting the best strategies to improve current processes.